2006
DOI: 10.1542/peds.2005-2621
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy in Youth With Type 1 Diabetes: A Retrospective Paired Study

Abstract: Continuous subcutaneous insulin infusion improves glycemic control in youth with type 1 diabetes, especially in those with a history of poor glycemic control. This improvement is associated with a decrease in the rate of severe hypoglycemia in the absence of weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 26 publications
(22 reference statements)
10
88
0
7
Order By: Relevance
“…Indeed, patients with poor control are often excluded from trials of insulin pump therapy. However, a number of RCTs and observational studies have revealed that this group frequently has the greatest improvement in glycaemic control with pump therapy [17,23,24]. These patients, moreover, are at greatest risk of developing complications and stand to benefit most from a reduction in HbA 1c [2].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, patients with poor control are often excluded from trials of insulin pump therapy. However, a number of RCTs and observational studies have revealed that this group frequently has the greatest improvement in glycaemic control with pump therapy [17,23,24]. These patients, moreover, are at greatest risk of developing complications and stand to benefit most from a reduction in HbA 1c [2].…”
Section: Discussionmentioning
confidence: 99%
“…He and his team accumulated a lot of experience with the different age groups ''studying'' pumps in toddlers, children, prepubertal children, and children during puberty and in those with advanced puberty, meaning young adults. Their publication 31 showed that switching children and young adults from MDI to a pump has a long-lasting effect. ''Those with higher HbA1c showed the maximum effect of the pump on their diabetes control without penalty in severe hypoglycemia,'' Phillip said.…”
Section: Insulin Pump Therapy In the Management Of Type 1 Diabetes-cumentioning
confidence: 99%
“…An increasing number of studies have shown a beneficial effect on glycaemic control with CSII compared with MDI (52)(53)(54)(55)(56)(57). In addition, observational trials in children have shown a decrease in the rate of severe hypoglycaemic episodes with CSII, despite decreasing HbA1c values (55,(58)(59)(60).…”
Section: Insulin Pumpsmentioning
confidence: 99%
“…In addition, observational trials in children have shown a decrease in the rate of severe hypoglycaemic episodes with CSII, despite decreasing HbA1c values (55,(58)(59)(60). Furthermore, evidence indicates that quality of life and patient satisfaction with CSII therapy are at least equal to or greater than that achieved with MDI (61-64).…”
Section: Insulin Pumpsmentioning
confidence: 99%